1996
DOI: 10.1128/iai.64.6.2031-2040.1996
|View full text |Cite
|
Sign up to set email alerts
|

Potential role of molecular mimicry between Helicobacter pylori lipopolysaccharide and host Lewis blood group antigens in autoimmunity

Abstract: Helicobacter pylori is involved in gastritis, gastric and duodenal ulcers, gastric adenocarcinoma, and mucosaassociated lymphoid tissue lymphoma. Earlier studies already suggested a role for autoimmune phenomena in H. pylori-linked disease. We now report that lipopolysaccharides (LPS) of H. pylori express Lewis y, Lewis x, and H type I blood group structures similar to those commonly occurring in gastric mucosa. Immunization of mice and rabbits with H. pylori cells or purified LPS induced an anti-Lewis x or y … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
164
0
7

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 396 publications
(179 citation statements)
references
References 40 publications
8
164
0
7
Order By: Relevance
“…Based on the molecular mimicry between host and H. pylori, bacterial expression of Lewis blood group antigens has also been suggested to play a role in the pathogenesis of H. pylori. 6 We previously demonstrated that PU disease in Singapore population is associated with increased expression of Lewis blood group antigens in H. pylori. 7 The present study confirmed that such an association also holds true for the H. pylori strains in China.…”
Section: Discussionmentioning
confidence: 97%
“…Based on the molecular mimicry between host and H. pylori, bacterial expression of Lewis blood group antigens has also been suggested to play a role in the pathogenesis of H. pylori. 6 We previously demonstrated that PU disease in Singapore population is associated with increased expression of Lewis blood group antigens in H. pylori. 7 The present study confirmed that such an association also holds true for the H. pylori strains in China.…”
Section: Discussionmentioning
confidence: 97%
“…For example, the C-type Lectin DC-SIGN recognizes a wide variety of microorganisms through binding of mannose or antigens that structurally resemble the carbohydrate structures of Lewis antigens [12]. The hypothesis of molecular mimicry existing between Helicobacter pylori (and possible other bacteria) lipopolysaccharide that expresses Lewis blood group antigens and host glycoconjugates possibly giving rise to autoimmune phenomena, as suggested by Appelmelk et al [9], featured in the pathogenesis of T1D. This hypothesis proposes autoimmunity to be induced by (bacterial) gastrointestinal infection breaking tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…To resolve this apparent inconsistency, we set out to determine phenotypically the prevalence of the Lewis (negative) phenotypes in undisputedly Type 1 diabetic (T1D) patients and compare this with control populations. An association of Le with T1D would be of interest, as this blood group has been proposed to be linked to the intestinal flora and mucosal immunity, with implications for autoimmune disease [9].…”
Section: Introductionmentioning
confidence: 99%
“…42 Different autoimmune disorders have been associated with H. pylori infection, and molecular mimicry was proposed as a triggering mechanism in some of them. Appelmelk et al 43 observed that immunization of mice and rabbits with H. pylori lipopolysaccharide elicited production of antibodies to Lewis blood group antigens, which recognized human and murine gastric glandular tissue. Amedei et al 44 showed that cell clones of gastric T cells recovered from H. pylori-infected patients with autoimmune gastritis recognized both pathogen antigens and H + , K + ATPase.…”
Section: Bacteriamentioning
confidence: 99%